Meningkatkan Minat Belajar Siswa terhadap Pola Asuh Orang Tua pada Anak Sekolah Dasar - Denabila, Esa; Nabila, Putri; Zuliani, Rizki (Lembaga Yasin AlSys, 2023)
Learning is an activity that is carried out by someone intentionally in a conscious state to obtain a new concept, understanding, or knowledge so that it allows a person to change behavior that is relatively constant both in thinking, feeling and acting. The learning outcomes obtained by students vary, because they are influenced by various factors, both internal and external factors. Interest is the tendency of one's soul towards an object, usually accompanied by feelings of pleasure, because it feels there is an interest in that something. parenting style in the family means the habits of parents, father or mother in leading, nurturing and guiding children in the family. Classroom action research is casuistic research and contextualizes conditions, using the spiral model by Kemmis and Mc. Taggart. The sample in this study were all fourth grade students at SDN Kunciran 7 Tangerang City with research instruments in the form of tests and observations. Interview or interview sampling techniques, observation and documentation. The data analysis technique used in this study is an interactive model analysis consisting of four data analysis components, namely data collection, data reduction, data presentation and drawing conclusions. The results of this study are that the learning outcomes of fourth grade students at SDN Kunciran 7 Pinang District are still relatively low. One of the factors that influence student learning outcomes is the family environment factor. This was obtained from the overall data of the fourth grade students, out of 61 students, more than half of the students, namely 32 students, received an average score below the KKM.